2018
DOI: 10.3390/molecules23092398
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Improves Bone Histomorphology and Prevents Bone Loss in Ovariectomized Diabetic Rats by Upregulating the OPG/RANKL Ratio

Abstract: Postmenopausal diabetic women have a high risk of fractures. Salidroside has preventive effects on estrogen deficiency-induced osteoporosis and has hypoglycemic effects on diabetes in rats. However, whether salidroside inhibits bone loss in postmenopausal diabetic patients is still unknown. Here, we established a rat model of osteoporosis to investigate the protective effects of salidroside on bone loss induced by ovariectomy combined with diabetes, also investigating the underlying mechanisms. Two-month-old f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Non-fasting plasma glucose of diabetic mice was higher than that of non-diabetic mice significantly, as well as HbA1c. With regard to body weight of diabetic mice, it was lower than that of non-diabetic mice, similar to previous studies (33, 34). Thus, the diabetic animal model was constructed successfully.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Non-fasting plasma glucose of diabetic mice was higher than that of non-diabetic mice significantly, as well as HbA1c. With regard to body weight of diabetic mice, it was lower than that of non-diabetic mice, similar to previous studies (33, 34). Thus, the diabetic animal model was constructed successfully.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies, CTX-1, the serum bone resorption marker, was increased in diabetic mice, which may suggest enhanced osteoclast differentiation (35). Interesting, different from bone formation biomarkers in vitro , the expression of ALP, osteocalcin, and PINP in the serum were increased in diabetic mice, which can be explained by the theory that osteoblasts was stimulated to compensate for the insulin depletion-related bone loss (33). The same situation of increased ALP is also found in diabetes patients, which is explained by the matrix hypermineralization (22, 23).…”
Section: Discussionmentioning
confidence: 98%
“…It could be divided into bone formation markers and bone resorption markers [32]. ALP, PINP and osteocalcin are bone formation markers representing the metabolic products of osteoblasts activity and bone formation; CTX-1 and TRACP 5b are bone resorption markers, representing the metabolites of osteoclasts activity and bone resorption, especially the degradation products of bone matrix [33]. In this study, both bone formation and bone resorption markers increased in diabetic rats, indicating an accelerated bone turnover in diabetes.…”
Section: Discussionmentioning
confidence: 52%
“…It is well accepted that the serum specific biomarkers of bone formation (ALP) and bone resorption (TRAP) are widely selected to assess the bone remodeling [ 30 ]. Zheng et al reported that a significantly increased serum ALP levels in the ovariectomized diabetic rats compared with the control [ 31 ], and Liu et al found that a decrease in TRAP level in serum was observed in diabetic rats with Mori Folium treatment [ 32 ]. Intriguingly, we found that the up-regulation of ALP and TRAP were markedly alleviated by LWDH and alendronate (ALN) treatment.…”
Section: Discussionmentioning
confidence: 99%